Governments Policy Reforms from 1970s Onward and It’s Implications on Land Use and Land Cover With the Help of GIS And RS Techniques In Eastern Tigray, Ethiopia - Tilahun, Abineh; Teferie, Bogale (International Journal of Geography and Geology, 2015)
The few policies that existed to stop the accelerating rate of land degradation were poorly enacted because institutions involved in land-related policies changed frequently. Three different governments have been in power in Ethiopia since 1972, and the policies implemented by each have directly affected land use. To do this, the studies analyze the LULC changes by considering the major political and policy reforms from 1970s. For this study, four LANDSAT images covering over a period of 1972 (Landsat-1 MSS); 1984 (Landsat-5 TM); 2000 (Landsat-7 ETM+) and 2014 (Landsat-8 OLI_TIRS) was used and analyzed using Arc GIS 10.1 and Erdas Imagine 13. Supervised classification system was used to classify the images of different land use categories. Generally Farm land, Settlement land, Grazing land, Forest land, Bush land, Water bodies and Bare/stony land was identified. The result shows that there is decreasing of Bush land from the year 1972 to 2014 and forest land from the year 1984 to 2014. And there was increasing of Agriculture and settlement from the year 1972 to 2014.